The Rationality of Renaissance Magic. - Dawes, Gregory W. (Parergon, 2013)
Belief in magic is widespread both in history and in contemporary cultures. Can such belief be regarded as rational? If so, in what way?An examination of the magic of Renaissance Europe enables us to distinguish three ways in which a belief can be rational. It can be (a) rationally defensible, given a particular set of background beliefs, (b) formed by some reliable means, or (c) the result of procedures that are collectively rational. Distinguishing these different forms of rationality not only helps us to understand magical thought; it also assists in the controversial task of distinguishing magic from science.